Political Contestation of Territorialization Between Conventional and Online Transportation Services in Bali Tourism Industry - Tedi Erviantono; Muhammad Ali Azhar (Universitas Sultan Ageng Tirtayasa, 2023)
This article describes the political contestation of territorialization between conventional and online transportation services in pursuing space in the tourism industry in Bali. This article utilized an institutionalism-constructivist theoretical approach. The method is a qualitative approach with data collection by observation, interviews, and documentation. The results show that the tourism industry in Bali has encouraged new space for actors pursuing political and economic interests, especially after the inclusion of online transportation in areas that are convenient for actors who operate behind conventional transportation services supporting tourism. They actively form new institutions against the dominance of online transportation services by creating their governance amid regulations. Under the cooperative institution, governance is run by actors who control the two modes of transportation services. They include regional tourism associations (Sanur, Kuta, Canggu, Ubud, and Nusa Dua), airports, hotels, villages, and terminals. These modes of transportation services negotiate their respective political and economic interests.